2018
DOI: 10.1177/0192512118772852
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impacts of parliamentary gender quotas in a single-party system: Symbolic co-option or delayed integration?

Abstract: In recent years scholars have shifted their attention from the causes behind parliamentary gender quotas to their consequences for women’s descriptive, substantive, and symbolic representation. We contribute to this literature by focusing on long-term effects of gender quotas in the context of an authoritarian one-party system. Here we contest dominant theoretical explanations which posit that gender quotas in authoritarian states primarily serve the goals of symbolic co-option and window-dressing. Rather, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although there have been recent instances of women receiving more 'masculine' posts, like defence (Barnes and O'Brien 2018;Barnes and Taylor-Robinson 2018), such cases are rare, and the gendered division of labour persists at both the national (Kroeber and Hüffelmann 2022) and the subnational level (Tremblay and Stockemer 2013). The pattern is especially noticeable when women are new to the institution, but it is likely to diminish as women's representation increases, as evidenced by studies of five Arab parliaments and the case of Vietnam (Joshi and Thimothy 2019;Shalaby and Elimam 2020). The gendered division of labour has affected women's advancement.…”
Section: Gender In Executive Appointmentsmentioning
confidence: 99%
“…Although there have been recent instances of women receiving more 'masculine' posts, like defence (Barnes and O'Brien 2018;Barnes and Taylor-Robinson 2018), such cases are rare, and the gendered division of labour persists at both the national (Kroeber and Hüffelmann 2022) and the subnational level (Tremblay and Stockemer 2013). The pattern is especially noticeable when women are new to the institution, but it is likely to diminish as women's representation increases, as evidenced by studies of five Arab parliaments and the case of Vietnam (Joshi and Thimothy 2019;Shalaby and Elimam 2020). The gendered division of labour has affected women's advancement.…”
Section: Gender In Executive Appointmentsmentioning
confidence: 99%
“…In terms of traditional ideological cleavages, several studies have found left-leaning parties in Asia to be generally more supportive of women's issues and women candidates than right-leaning parties (e.g. Haque 2003;Stockemer 2009;Joshi & Kingma 2013;Joshi 2015;Joshi & Thimothy 2019;Eto 2021). In the case of Western countries, studies often find newer center-left parties (e.g.…”
Section: Substantive Representation Of Womenmentioning
confidence: 99%
“…Both are relatively economically underdeveloped, in a post-conflict setting with high rates of poverty and have only recently instituted one-third gender quotas for women MPs. The long-term effects of these quotas are still uncertain, but similar post-conflict gender quotas in Asia have exhibited positive effects as seen in Vietnam (Joshi & Thimothy 2019).…”
Section: Conclusion: Revisiting Our Hypothesesmentioning
confidence: 99%